On the band gap location and core spectra of orthorhombic IV-VI compounds SnS and SnSe - Makinistian, Leonardo (2009)
While the orthorhombic IV–VI compounds show the typical layered behavior of that crystallography, we show that the presence of sulphur induces important changes to the band gap behaviour: both in its location, and in its character as well. Our modelling of tin sulfide (SnS) and tin selenide (SnSe), performed within an ab initio density-functional theory (DFT) with a FP-LAPW method, shows that the spin–orbit interaction produces slight splittings of bands in both compounds, especially in the conduction band, which are in very good agreement with measured values of the core spectra. In addition to these splittings, for SnS we found the novel feature that the spin–orbit relocates the band gap in the BZ, while it does not affect that of SnSe. Furthermore, several aspects of the crystals anisotropy may be explained upon our results on the hybridized band structure, the density of states (DOS) and the optical spectra (complex dielectric function and absorption coefficient). We satisfactorily compare our results with those available in the literature.